Maxillofacial Manifestation of a Giant Dimension Cranial Osteoma - Guerra, Raphael Capelli [UNESP]; Carvalho, Pedro Henrique de Azambuja [UNESP]; Pulino, Bianca de Fátima Borim [UNESP]; Passetto, Marcelo Teixeira; Junior, José Carlos Rodrigues; Hochuli-Vieira, Eduardo [UNESP] (Wolters Kluwer, 2020)
Osteoma is the most frequent benign tumor in the craniomaxillofacial region. The most common initial manifestation is facial pressure or headache.The clinical examination showed increased volume in the right supraorbital region, asymmetry of the orbital contour, exophthalmia, dystopia, proptosis and clinical restraint of ocular movement for supraversion. The lesion measured approximately 4 cm in diameter with irregular contour. Osteotomy was performed with saw surrounding the tumor, with aid of a surgical piezo on the orbital medial wall.The result of histopathological examination was osteoma. The patient is 2.5 years postoperatively and so far without complications.